Value chain analysis of vegetables: The case of Ejere District, West Shoa Zone, Oromia National Regional State of Ethiopia - Hailu, A. (Haramaya University, 2016)
This research attempted to analyze value chain of vegetables in Ejere district, Oromia Region of Ethiopia focusing on potato and onion crops. Potato and onion plays a significant role in increasing food security and income for the poor farmers of Ethiopia. Data for the study were collected from both primary and secondary sources. The primary data were generated by household survey using a pre-tested structured questionnaire and key informant interview using checklists. The data were collected from 120 farmers, 30 traders and 35 consumers and analyzed using STATA software. Vegetables value chain actors identified in the study include input suppliers, producers, rural collectors, brokers, retailers, wholesalers, processors and consumers. The chain is governed mainly by wholesalers with the assistance of brokers. Producers are price takers and hardly negotiate the price due to fear of post-harvest loss, in case the product is not sold. Five and six market channels were identified for potato and onion, respectively. The highest total gross margins are 53.78% in channel II for potato and 32.55% in channel II for onion. The highest gross marketing margin of producers in potato and onion markets channels are 65.76% and 72.84% in channel III and V, respectively. The two-stage least square regression model results showed that five variables such as productivity of potato, sex of household head, distance to nearest market, off/non-farm income and area of land allocated for potato significantly affect the volume of potato supplied to the market while four variables such as productivity of onion, education level, farming experience and land allocated for onion significantly affect the volume of onion supplied to the market. The multivariate probit model results indicated that quantity of potato sold, education level, sex of households head, family size, farming experience, distance to nearest market, off/non-farm income, trust in traders, ownership of motor pump, selling price of potato and area of land allocated for potato significantly influence potato producers choosing of market outlets for their produce while quantity of onion sold, extension contact, farming experience, distance to nearest market, non/off-farm income, selling price of onion, trust in traders, ownership of motor pump and land size allocated for onion were among determinants which affect significantly onion producers choice of alternative market outlets. Policy implications drawn from the study findings include the need to improve the input supply system,, improving farmers’ knowledge and experience on vegetable production, encouraging adult education through extension service, improving productivity and volume sales of vegetables, strengthening the linkage/interaction among vegetables value chain actors, expanding accessibility of market infrastructure and strengthening supportive institutions.